Efficacy and safety of esketamine in preventing perioperative neurocognitive disorders: a meta-analysis of randomized controlled studies - Kuo-Chuan Hung; Chia-Li Kao; Chun-Ning Ho; Jheng-Yan Wu; Ying-Jen Chang; Chien-Ming Lin; I-Wen Chen (Systematic Reviews)
Abstract Background Perioperative neurocognitive disorders (POND) are common in older adults and are associated with adverse outcomes. This meta-analysis aimed to evaluate the efficacy and safety of esketamine for the prophylaxis of POND. Methods Electronic databases were comprehensively searched from inception to April 1, 2024, to identify randomized controlled trials (RCTs) exploring the impact of perioperative esketamine on POND in adult patients. The primary outcomes were the incidence of POND and the level of postoperative cognitive function. The secondary outcomes included recovery characteristics (i.e., respiratory depression, extubation time, agitation, hallucinations, and nightmares) and inflammatory markers. Subgroup and meta-regression analyses were conducted to investigate the heterogeneity and effect of esketamine dosage. Results A total of 24 RCTs (n = 2,130 patients), all conducted in China with relatively short follow-up periods (≤ 3 months), were included. Esketamine was found to significantly reduce the risk of POND (risk ratio:0.53, 95%confidence interval [CI]: 0.43–0.67) and improved cognitive function on postoperative day 1 (standardized mean difference [SMD]:1.22, 95%CI:0.85–1.59) and day 3 (SMD:0.94, 95%CI: 0.46–1.43) compared with controls, without impacting recovery characteristics. Furthermore, esketamine was associated with lower pain scores, reduced risk of postoperative nausea/vomiting, and decreased levels of inflammatory markers (IL-6, TNF-α, and S100β). Subgroup and meta-regression analyses revealed that age, quality of studies, type of esketamine administration, and esketamine dosage did not have a significant impact on cognitive outcomes. The evidence showed moderate certainty for POND risk, low certainty for POD 1 cognitive function and several complications (agitation, hallucinations, PONV, respiratory issues, nightmares) and biomarkers (TNF-α, s100β), and very low certainty for POD 3 cognition, extubation time, pain, and IL-6 levels. Conclusion Perioperative esketamine is potentially effective in reducing the risk of POND and improving cognitive function in adult patients, regardless of age and dosage. Nevertheless, the certainty of evidence was low to very low for several outcomes (e.g., cognitive function on POD 3). Given that all included studies were conducted in China with relatively short follow-up periods, further high-quality RCTs with diverse populations and longer follow-up are warranted to validate these findings.